2020
DOI: 10.1080/00365513.2020.1730433
|View full text |Cite
|
Sign up to set email alerts
|

Substantial inter-individual variations in insulin secretion and sensitivity across the glucometabolic spectrum

Abstract: Impaired insulin secretion and action are important for development of type 2 diabetes (T2D) and metabolic syndrome (MetS). Despite recognized heterogeneity of these glucometabolic disorders, few data are available of biological variation in insulin secretion and action among individuals with T2D and MetS. The aim of this study was to explore the inter-individual variations using gold standard methods in a cross-sectional study of two independent cohorts of phenotypically well-characterized subjects. Cohort I … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…However, these results should be interpreted with caution because in Zamuner et al (2020a) we found no difference in peripheral tissue response to insulin between goats of different basal insulin levels (5.6 vs. 12.9 mU/L, P = 0.008). Therefore, the observed large interindividual variations in insulin production and secretion could be attributed to genetic differences, as has been demonstrated in humans (Hansen et al, 2020), or to differences in milk production and energy status (Zamuner et al, 2020a). Nevertheless, the reasons for the present findings remain speculative.…”
Section: Comparison Of Measures Of Insulin Sensitivity In Early-lactation Dairy Goatsmentioning
confidence: 68%
“…However, these results should be interpreted with caution because in Zamuner et al (2020a) we found no difference in peripheral tissue response to insulin between goats of different basal insulin levels (5.6 vs. 12.9 mU/L, P = 0.008). Therefore, the observed large interindividual variations in insulin production and secretion could be attributed to genetic differences, as has been demonstrated in humans (Hansen et al, 2020), or to differences in milk production and energy status (Zamuner et al, 2020a). Nevertheless, the reasons for the present findings remain speculative.…”
Section: Comparison Of Measures Of Insulin Sensitivity In Early-lactation Dairy Goatsmentioning
confidence: 68%
“…Furthermore, by using material from different donors, for instance, with and without T2DM, NAFLD or metabolic syndrome, the established model provides an appealing system to parse the molecular basis for interindividual differences in insulin sensitivity and secretion across the glucometabolic spectrum, which are known to be extensive. [110] Combined, we have developed a versatile modular chip platform with pneumatic actuation that allows for controlled reciprocal mass transfer between different tissue models at physiologically relevant compartment-specific flow rates. By establishing an integrated coculture of healthy organotypic primary human liver spheroids and intact primary human islets, we demonstrate functional tissue crosstalk.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, by using material from different donors, for instance, with and without T2DM, NAFLD or metabolic syndrome, the established model provides an appealing system to parse the molecular basis for interindividual differences in insulin sensitivity and secretion across the glucometabolic spectrum, which are known to be extensive. [ 110 ]…”
Section: Discussionmentioning
confidence: 99%
“…First, it is well documented that there are individual differences in beta cell function (45,46), which contribute to differences in the degree of insulin and c-peptide secretion (recall that insulin and c-peptide are co-secreted in equimolar amounts). While this difference is most pronounced in conditions such as metabolic syndrome and type 2 diabetes (47), individual differences in the secretory capacity of the beta cell in healthy individuals have been reported as well (48,49). Another important consideration is that at least 70% of total secreted insulin and c-peptide is released in a pulsatile manner (50) with a typical period of about 5 minutes (51,52).…”
Section: Discussionmentioning
confidence: 99%